Anomalous formation of micrometer-thick amorphous oxide surficial layers during high-temperature oxidation of ZrAl2. Issue 7 (July 2019) - Hu, Zhangping; Xu, Yifei; Chen, Yuanyuan; Schützendübe, Peter; Wang, Jiangyong; Huang, Yuan; Liu, Yongchang; Wang, Zumin
Abstract: The thermal oxidation of ZrAl2 in the temperature range of 550–750 °C in pure oxygen has been investigated by a combinational experimental approach using X-ray diffraction, scanning electron microscopy/energy dispersive spectrometer, Auger electron spectroscopy and cross-sectional transmission electron microscopy. The thermal oxidation leads to the growth of anomalously thick (up to 4.5 μm) amorphous (Zr0.33 Al0.67 )O1.66 surficial layers at temperatures as high as 750 °C. The oxidation kinetics obeys a parabolic law with an activation energy of 143 kJ/mol. The underlying mechanism for the formation of such micrometer-thick amorphous oxide surficial layers has been discussed on the basis of interface thermodynamics and the occurrence of high interface stability associated with a synchronous oxidation of Al and Zr elements.